A low power wideband differential transimpedance amplifier for optical receivers in 0.18-μm CMOS - Seng, Chong Whye. (2013)
This paper presents a low power wideband differential TIA for optical receivers. The wideband operation is achieved by modifying a conventional regulated cascode input stage and combining it with a feedback amplifier in a 0.18μm CMOS process. The post-layout simulation results show that the proposed TIA has a bandwidth of 4.5 GHz, average input referred noise current spectral density of 13.7 pA/sqrtHz from DC to 7 GHz, and transimpedance gain of 64.8 dBO. The proposed TIA dissipates only 3.5 mW with a 1.8 V power supply. The core circuit occupies a chip area of 97 μm × 53 μm.